(untitled) (Herald of Journalism, 2020)
The article is devoted to the problems of the development of a knowledge society. The formation of an “intellectual nation” is a way of modernizing society in the 21st century, when creative individuals become the main source of development. “Intellectual nation project” should consider three potential points: creation of new solutions, technologies and innovations; information revolution; spiritual educa- tion of youth. Today Kazakhstan has enough features to take its rightful place in the sphere of training specialists competitive on the world stage. The purpose of this article is the production of fixed capital and the highest value – an individual, who is not only a professional, but also carries qualities and properties of his spiritual and moral person- ality. The article carried out a systematic and comparative analysis of the works of outstanding researchers who conducted research in the field of intellectual investments, intangible values, economic freedom, political freedom, mass communication and public interests, political discourse and metaphor, as well as analysis, discussion and evaluation of ways to form a national Kazakhstan’s potential. To increase the intellectual potential of Kazakhstan, it is necessary to create a knowledge society. Prerequisites contributing to this, consider increasing scientific and innovative potential, increasing ac- cess to education for the population, increasing access to informational equality for citizens. When working on the study, the authors applied the content analysis method in the theoretical part and the questionnaire method. The scientific novelty of this study is to develop recommendations for optimizing the impact of the media on life by the modern target audience of the formation of an intel- lectual nation. The practical significance of this study lies in the fact that its results can be used both in further theo- retical analysis of the problem and in the practice of organizing media.